Factors Associated with the Incidence of Vertigo in Konawe Distric - Biduri, Evi Nurmaisa; Saafi, La Ode; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2023)
Background: Based on data obtained from the Konawe District Health Office, it is known that there are still many women affected by Vertigo and each year it has increased. There were 2,460 cases recorded in 2020, in 2021 there were 2,770 cases, while in 2022 month 6 there were 2,890 cases. The purpose of this study was to analyze the factors associated with the incidence of vertigo in Konawe District. Methods: This research was a quantitative observation with using a Cross Sectional Study design. This research was carried out from October to November 2022. The research population was all people suffering from disabled neurological diseases at the Konawe district health office living in the Konawe district in 2021 totaling 698 cases with the sample is 97 respondents. Results: The results showed that the results of the chi-square test on the work fatigue variable obtained an X2 hit value = 23.642, stress obtained an X2 hit value = 25.630, and sleep patterns obtained an X2 hit value = 26.085. Conclusion: The conclusion was that there is a relationship between work fatigue, stress and sleep patterns with the incidence of vertigo in Konawe Regency, the most dominant variable associated with the incidence of vertigo is sleep pattern variable.